2021
DOI: 10.3390/hydrology8030142
|View full text |Cite
|
Sign up to set email alerts
|

Service Accessibility Risk (SAR) Assessment for Pluvial and Fluvial Floods in an Urban Context

Abstract: The development of strategies to adapt to and mitigate the potential adverse consequences of natural hazards requires support from risk assessment studies that quantify the impacts of hazardous events on our society. A comprehensive analysis of risk commonly evaluates the elements exposed to the hazard probabilistic scenarios and their vulnerabilities. However, while significant advances have been made in the assessment of direct losses, indirect impacts are less frequently examined. This work assesses the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, the research does not specify whether the region is categorized as a developed or developing country (Nkwunonwo et al, 2020). The impacts and effects of flash floods on both urban and non-urban areas were also found in a previous review (Arosio et al, 2021). It is observed that some studies assessing urban resilience with a disaster risk management approach have examined the effects of both natural and non-natural disasters (Wang et al, 2019).…”
Section: Current State Of the Researchmentioning
confidence: 70%
“…However, the research does not specify whether the region is categorized as a developed or developing country (Nkwunonwo et al, 2020). The impacts and effects of flash floods on both urban and non-urban areas were also found in a previous review (Arosio et al, 2021). It is observed that some studies assessing urban resilience with a disaster risk management approach have examined the effects of both natural and non-natural disasters (Wang et al, 2019).…”
Section: Current State Of the Researchmentioning
confidence: 70%
“…Hydrometeorological data are stored and and analyzed in the IoT cloud. We have used an open-source, portable, energy-efficient, reconfigurable, and scalable board that comprises of an ATmega328p microcontroller, Arduino UNO [29]. This board offers the advantage of onboard power supply regulation, facilitating voltage regulation without the need for additional circuitry.…”
Section: Architecture Of the Proposed Iot Systemmentioning
confidence: 99%
“…Preparation measures can include: (i) readiness for intervention; (ii) emergency operation and rescue; (iii) early-warning systems (EWSs); (iv) recovery and recondition. Whereas all these measures are essential [256][257][258], the need for an effective EWS to span all components, from hazard detection to community response, has been underlined in particular by the United Nations Framework Convention on Climate Change and through the Paris Agreement and the sustainable-development goals [230,231], as well as being further articulated in the Sendai Framework for Disaster Risk Reduction [229]. These documents highlighted the features and roles that should characterize an effective EWS, which are based on a set of capabilities needed to generate and disseminate timely and meaningful warning information to enable individuals, communities and organizations threatened by a hazard to prepare and act appropriately in sufficient time in order to reduce the possibility of harm or loss.…”
Section: Preparedness and Early-warning Systemsmentioning
confidence: 99%